Technospheric Mining of Mine Wastes: A Review of Applications and Challenges - Lim, Bona; Alorro, Richard Diaz (2021)
The concept of mining or extracting valuable metals and minerals from technospheric stocks is referred to as technospheric mining. As potential secondary sources of valuable materials, mining these technospheric stocks can offer solutions to minimise the waste for final disposal and augment metals’ or minerals’ supply, and to abate environmental legacies brought by minerals’ extraction. Indeed, waste streams produced by the mining and mineral processing industry can cause long-term negative environmental legacies if not managed properly. There are thus strong incentives/drivers for the mining industry to recover and repurpose mine and mineral wastes since they contain valuable metals and materials that can generate different applications and new products. In this paper, technospheric mining of mine wastes and its application are reviewed, and the challenges that technospheric mining is facing as a newly suggested concept are presented. Unification of standards and policies on mine wastes and tailings as part of governance, along with the importance of research and development, data management, and effective communication between the industry and academia, are identified as necessary to progress technospheric mining to the next level. This review attempts to link technospheric mining to the promotion of environmental sustainability practices in the mining industry by incorporating green technology, sustainable chemistry, and eco-efficiency. We argue that developing environmentally friendly processes and green technology can ensure positive legacies from the mining industry. By presenting specific examples of the mine wastes, we show how the valuable metals or minerals they contain can be recovered using various metallurgical and mineral processing techniques to close the loop on waste in favour of a circular economy.